Earthquake Disaster Risk Assessment Analysis In Jailolo Coastal Region - Rohima Wahyu Ningrum; Risky Nuri Amelia; Hasmawati Hasmawati; Marwis Aswan; Saprudin Saprudin (Universitas Khairun, 2021)
The village, which is located in the Coastal District of Jailolo, West Halmahera, had a considerable impact from the earthquake. This is because the earthquakes that occur are influenced by tectonic earthquakes due to the movement and collision of tectonic plates on land and the seabed. If the collision causes a fault in the seabed, a tsunami can occur. The purpose of this study was to analyze the risk of earthquake disasters in supporting development planning and to produce an earthquake risk map for the coastal area of Jailolo District, West Halmahera. The analytical method used is descriptive quantitative, and the data collection model is a questionnaire with random sampling. The results obtained are in the form of a hazard value using the PGA value and produce the same PGA value, namely > 0.70 gal with a high category for Bobanehena Village, Saria Village, Payo Village, Bobo Village, and Idamdehe Village. The value of vulnerability (physical, social, and economic vulnerability) shows that Bobanehena Village has a high vulnerability index value with a score of 1.9. The capacity index value for the five villages has the same score of 3 and is included in the high class. So that the value of the earthquake risk level with a high class is obtained, namely in Bobanehena Village and Bobo Village. The high level of risk in the two villages is influenced by the frequency of occurrence of earthquakes with high intensity in the area, the impact of losses due to earthquakes is quite high. Earthquake risk reduction efforts will be maximized if a comprehensive earthquake risk assessment analysis is carried out and a commitment from the Government is carried out.